2015
DOI: 10.1136/sextrans-2015-052270.177
|View full text |Cite
|
Sign up to set email alerts
|

O18.2 Injectable progestin contraception and acquisition of hsv-2 infection among south african women participating in the voice trial

Abstract: Background Of 270,000 new HIV infections in children, 90% are in Sub-Saharan Africa. High fertility levels and high number of women infected with HIV results in high rates of Mother-to-Child-Transmission (MTCT) in SSA. To date, most efforts to prevent MTCT of HIV have focused on the third prong, a strategy that offers ARV drugs to HIV infected pregnant women and their exposed infants. However, the effective use of contraceptives to prevent unwanted pregnancies among HIV-positive women has the ability to reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Of note with our data is that hormonal contraception includes injectable contraception and oral contraceptives, which have not shown an increased risk in HIV acquisition. One study evaluating the effect of hormonal contraception on risk of HSV-2 infection showed that injectable contraception did not increase this risk [32]. Further studies need to be conducted to confirm these findings.…”
Section: Discussionmentioning
confidence: 99%
“…Of note with our data is that hormonal contraception includes injectable contraception and oral contraceptives, which have not shown an increased risk in HIV acquisition. One study evaluating the effect of hormonal contraception on risk of HSV-2 infection showed that injectable contraception did not increase this risk [32]. Further studies need to be conducted to confirm these findings.…”
Section: Discussionmentioning
confidence: 99%
“…Herpes Simplex Viruses (Type 1 and Type 2) are the most common sexually transmitted infections (STIs) worldwide and they are responsible for a wide variety of clinical infections, including encephalitis, neonatal infections, and or visceral diseases [ 172 ]. About 500 million people are currently affected with HSV-2 worldwide and about 20 million new cases occur each year across the world [ 173 ]. In South Africa, about 31% of women between the ages 15–26 are infected with HSV-2, and 84% are women who are commercial sex workers in KwaZulu-Natal province [ 173 ].…”
Section: Application Of Dendrimers For the Treatment Of Viral Infementioning
confidence: 99%
“…About 500 million people are currently affected with HSV-2 worldwide and about 20 million new cases occur each year across the world [ 173 ]. In South Africa, about 31% of women between the ages 15–26 are infected with HSV-2, and 84% are women who are commercial sex workers in KwaZulu-Natal province [ 173 ]. The antivirals that are currently being used have developed resistance, hence there is an increasing need to improve antiviral drugs efficacy [ 174 ].…”
Section: Application Of Dendrimers For the Treatment Of Viral Infementioning
confidence: 99%